2018
DOI: 10.3390/biom8030050
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Delivery of Macromolecules into Human Cells by Improving the Endosomal Escape Activity of Cell-Penetrating Peptides: Lessons Learned from dfTAT and its Analogs

Abstract: Cell-penetrating peptides (CPPs) are typically prone to endocytic uptake into human cells. However, they are often inefficient at escaping from endosomes, which limits their ability to deliver cargos into cells. This review highlights the efforts that our laboratory has devoted toward developing CPPs that can mediate the leakage of endosomal membranes, and consequently gain better access to the intracellular milieu. In particular, we have identified a CPP named dimeric fluorescent TAT (dfTAT) with high endosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 40 publications
0
33
1
Order By: Relevance
“…Evaluation of antigen cross‐presentation in BMDCs demonstrated the incorporation of Tat peptide enhance antigen cross‐presentation capacity of nanofibers. It is well‐known that CPPs with highly positive charges and alpha‐helical structures such as the Tat peptide can efficiently deliver fused cargo from the endosome to the cytosol by membrane fusion (Allen, Brock, Kondow‐McConaghy, & Pellois, 2018; Yamashita et al, 2016), so that increasing the number of CPP copies in the cargo leads to increased cytoplasmic delivery (Allen et al, 2018; Yamashita et al, 2016). Similar to our results, other studies suggested that the fusion with the Tat peptide, or combining the target antigen with other lysosomal lytic agents (i.e., polyethylenimine (PEI) could prompt antigen cross‐presentation (Bae et al, 2009; A. W. Li et al, 2018; J. Liu et al, 2018; Z. Liu et al, 2017; Su et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of antigen cross‐presentation in BMDCs demonstrated the incorporation of Tat peptide enhance antigen cross‐presentation capacity of nanofibers. It is well‐known that CPPs with highly positive charges and alpha‐helical structures such as the Tat peptide can efficiently deliver fused cargo from the endosome to the cytosol by membrane fusion (Allen, Brock, Kondow‐McConaghy, & Pellois, 2018; Yamashita et al, 2016), so that increasing the number of CPP copies in the cargo leads to increased cytoplasmic delivery (Allen et al, 2018; Yamashita et al, 2016). Similar to our results, other studies suggested that the fusion with the Tat peptide, or combining the target antigen with other lysosomal lytic agents (i.e., polyethylenimine (PEI) could prompt antigen cross‐presentation (Bae et al, 2009; A. W. Li et al, 2018; J. Liu et al, 2018; Z. Liu et al, 2017; Su et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Some other recently described approaches for endosomal escape include, but are not limited to, the formulation of pH buffering particles which build up the osmotic pressure and exhibit osmolytic endosomal escapemembrane disrupting particles which destabilize the membrane and gelatinous nanoparticles which exhibit endosomal escape via swelling and endosomal rupturing mechanisms (Cupic et al, 2018). Especially for charge containing drugs and carriers, the incorporation of a charged molecule inside the membrane which leads to the breakdown of membrane symmetry, creating alterations and disturbances in the electrostatic interactions, alterations of the protonation levels of pH responsive drug delivery systems, charge mediated changes in the membrane tension and consequent membrane ruptures, and ion mediated changes in the osmotic pressure inside endosomes are some of the recently studied mechanisms for endosomal escape (Tian and Ma, 2012;Lönn et al, 2016;Allen et al, 2018).…”
Section: Endosomal Escape Of Drugs and Carrier Systems For Subcellulamentioning
confidence: 99%
“…A potential strategy for enabling permeability of these peptides relies on attachment of a linear cell penetrat-ing peptide (CPP), such as Arg9 20 , Tat 21 , or Penetratin 22 , for cellular uptake 23,24 . While standard CPPs do enable permeability of some cargos, endosomal entrapment remains an issue [25][26][27][28] . Furthermore, CPPs have been tested in clinical trials, but so far none of these trials have led to an FDA-approved CPP conjugate 24 .…”
Section: Cyclic Cell-penetrating Peptides Tailor-made For the Creatimentioning
confidence: 99%